Hubungan Karakteristik Demografi Dengan Kepatuhan Minum Obat Pada Pasien Hipertensi Primer Di Unit Rawat Jalan RS X Bekasi - Maria Astrid; Nurjanah nurjanah; Indriati Kusumaningsih (Elisabeth Health Jurnal, 2021)
Introduction : Hypertension is a condition where the systolic blood pressure is more than 140 mmHg and the diastolic blood pressure is more than 90 mmHg. The purpose of this study was to determine the factors associated with medication adherence in hypertension patients, such as age, gender, education level, employment status and length of suffering from hypertension. Method : This study used a quantitative correlation method (cross sectional design). Sampling of 56 respondents was carried out by distributing questionnaires to the outpatient unit of RS.X Bekasi. Measurement of medication adherence using the MMAS (Modified Morisky Adherence Scalemethod)which consists of 8 questions. The data analysis used was chi square and Kendal Tau-b. Result : From the results of the univariate analysis, it was found that the characteristics of the respondents the majority are 56-65 years old (39.3%), female (71.4%), highly educated (51.8%), have a job (44.6%) and have suffered from hypertension for 1-5 years. years (51.8%) and the adherence of patients taking medication was in the low adherence category (60.7%). Bivariate analysis of demographic characteristics related to medication adherence were age (p = 0.000), education (p = 0.013 and r = -0.320), and occupation (p = 0.005). Meanwhile, the unrelated demographic characteristics were gender (p = 0.550) and duration of suffering from hypertension (p = 0.123 and r = 0.192).. Conclusion : Various factors related to medication adherence in hypertensive patients in his study, including age, education and employment status. Compliance with taking medication of respondents in this study is still relatively low.